(untitled) (Innovaciones Educativas, 2024)
During the COVID-19 pandemic, higher education worldwide was forced to restructure itself according to guidelines established by the World Health Organization (WHO) to mitigate the impact of the pandemic on the population. Costa Rica was no exception. In the absence of a contingency plan, the University of Medical Sciences (UCIMED) underwent a transition from face-to-face to virtual teaching. This study focused on the challenges experienced by physical therapy and nutrition faculty during the period from March to June 2020, due to the emergency virtualization. The information was collected through a Google Forms® survey; once tabulated, the data was analyzed, interpreted and compared between the professions, implementing descriptive statistics and a bibliographic review to better understand the situation at a global level. The study showed that the didactics of the course was a great challenge for the teachers, mainly in terms of learning assessment, student participation, use of virtual tools and connectivity problems. When comparing professions, it was found that limited training, fewer years of teaching experience, and less interaction with virtual platforms were factors that increased the perception of challenges. Confronting the challenges enriched the teaching experience in terms of ICT management and thus the transformation of higher education.